Smart Cable-Driven Camera Robotic Assistant. - Rivas-Blanco, Irene; López-Casado, Carmen; Pérez-del-Pulgar-Mancebo, Carlos Jesús; García-Vacas, Francisco; Fraile, Juan Carlos; Muñoz-Martínez, Víctor Fernando (IEEE, 2017)
This paper describes the mechanical design and a cognition system for a novel concept-of-camera robotic assistant. The system combines the advantages of intra-abdominal devices and autonomous camera navigation. The robotic assistant is composed of a magnetic intra-abdominal camera robot with two internal cable-driven degrees of freedom and an external robot that handles an external magnet. The intelligence of the robot is implemented in a cognitive architecture based on a long-term memory that stores the robot's knowledge and learning capabilities to improve the robot's behavior. The navigation strategy combines a reactive control based on instrument tracking and a proactive control based on predefined behaviors, depending on the actual state of the task. The robot's learning capabilities include a semantic customization, to adapt the camera's behavior to the surgeon's preferences, and reinforcement learning, to improve the camera navigation strategy. This paper details both the hardware implementation of the system and the software implementation in a robotic operating system architecture. The cognition system and the performance of the cable-driven mechanism have been validated with a set of in vitro experiments. Moreover, the camera robot has been evaluated through an in-vivo experiment in a pig.
Keywords: Visión artificial (Robótica); Cirugía - Innovaciones tecnológicas; Surgery; Navigation; Cameras; Robot vision systems; Tools